INCREASING TEACHER MOTIVATION IN CREATING AN INTERACTIVE LEARNING MEDIA BY USING GROUP TECHNIQUE COUBSELIUNG THROUGH EORKSHOP AT SMPN 38 BEKASI - Fitriati, Titi Kurnia (Krisnadwipayana International Journal of Management Studies, 2021)
This study aims to: 1) To find out the application of group guidance techniques in preparing lesson plans and interactive learning media to improve the professional competence of teachers at SMPN Bekasi City. 2) To find out the improvement of teacher competence in making interactive learning media through group guidance activities. The subjects of this study were all teachers of SMPN 38 Bekasi City. This research is a School Action Research (PTS) which consists of two cycles, each cycle includes the stages of planning, implementation, observation, and reflection. The data analysis technique used is comparative descriptive. The results of the study can show that the school must deliver an announcement to the teacher about the implementation of group guidance activities by making interactive learning media (b) The school must provide guidance material in the form of implementing learning accompanied by simulations; (c) The school prepares group guidance instruments without interfering with learning activities; and d) Conducting observations in class when group guidance activities are carried out by teachers to improve the professional competence of teachers at SMPN 38 Bekasi City in making interactive learning media. Workshop activities can motivate teachers to create interactive learning media with group guidance techniques.